Albert Camus, The stranger - McCarthy, Patrick 1941-2007 (Cambridge Univ. Pr., 1988)
Patrick McCarthy places The Stranger in the context of a French and French-Algerian history and culture, examines the way the work undermines traditional concepts of fiction, and explores the parallels (and more importantly the contrasts) between Camus and Sartre. His account provides a useful companion to The Stranger for students and general readers.
Keywords: Camus, Albert <1913-1960> / Étranger; Camus, Albert, 1913-1960 / Etranger; Camus, Albert <1913-1960> -- Etranger; Camus, Albert -- 1913-1960 -- L' étranger; L'étranger (Camus)